Literature Review on Malaysia National Food Security: Challenge And Strategy in Meeting Population Rise - Azri, Nur Shahirah binti Azlan; Rahman, Azrul Azlan Abd; Yasid, Amer Fawwaz Mohamad; Alias, Mohd Salman bin; Hamid, Nor Fazilah Abdul (Journal of Ecohumanism, 2025)
This research examines Malaysia’s national food security, focusing on the challenges posed by rising population, global disruptions, and the need for sustainable strategies. The primary objective is to analyze the effectiveness of Malaysia’s current food security measures in light of the growing population and increasing demand for food. Through qualitative methodologies, including document analysis and case studies, the study investigates the role of government policies, agricultural productivity, and technological adoption in ensuring food sustainability. The findings highlight Malaysia’s dependency on food imports, aging farmer demographics, and the lack of investment in agricultural research and development as key factors threatening food security. Additionally, disruptions such as the COVID-19 pandemic and geopolitical conflicts, such as the Russia-Ukraine war, exacerbate vulnerabilities. The research emphasizes the need for comprehensive policies, enhanced private investment, and technological advancements to build resilience in the nation’s food systems.